Exploring friends with benefits: a review of research and insights from the Polish context - Maciocha, Agnieszka; Wdowiak, Krystian; Wąż, Julia; Witas, Aleksandra; Drogoń, Justyna; Chachaj, Weronika; Gardocka, Ewa (Journal of Education, Health and Sport, 2024)
Introduction and Objective :"Friends with benefits" relationships (FWBR) are becoming increasingly common. Defined as friendships involving sexual activity without romantic commitment, FWBRs blur the boundaries between friendship and romance. The aim of this article is to gather the most up-to-date information on "friends with benefits" relationships. Review Methods: A review of studies available on the PubMed platform (https://pubmed.ncbi.nlm.nih.gov/) was conducted, including articles with free full-text access that used the keywords: “friends with benefits relationship”, “friends with benefits,” "FWB," and "FWBR." Brief Description of the State of Knowledge: Many individuals involved in friends with benefits relationships establish their own rules, and one surprising trend is the frequent observance of sexual exclusivity. Research on the prevalence of FWBRs has focused largely on students in the USA, but there is limited data on FWBRs in Poland, where they appear to be rising in popularity, influenced by dating sites and population migrations. Studies indicate that men, residents of larger cities, and less religious individuals are more likely to participate in FWBRs. Summary: FWBRs offer a unique dynamic where individuals can avoid the emotional commitments and negative traits of traditional romantic relationships. However, these relationships also present challenges, such as differing expectations between the partners and the societal stigma that may be associated with them.